NF-κB p65 and TCF-4 interactions are associated with LPS-stimulated IL-6 secretion of macrophages - Ji-Youn Kim; Hyeon-Gun Jee; Ju Yeong Kim; Tai-Soon Yong; Soung-Hoo Jeon (Biochemistry and Biophysics Reports, 2024)
Proinflammatory cytokine plays a central role in host defense and acute inflammatory responses. Both positive and negative correlations of NF-κB and Wnt/β-catenin pathways have been reported depending on cell types in response to inflammatory stimuli for IL-6 cytokine production. Macrophages are vital to the regulation of immune responses and the development of inflammation, but the crosstalk between two pathways has not been elucidated so far in macrophages. We observed a positive cross-regulation between the NF-κB and Wnt/β-catenin pathways for IL-6 production in human macrophages. To verify the functional validity of this interaction, LY294002 or PNU74654, representative blockers of each pathway, were treated. IL-6 secretion was reduced to the basal level by both inhibitor treatments, even when stimulated by LPS. We also found that NF-κB p65 migrated to the nucleus and interacted with the transcription factor TCF-4 in macrophages upon LPS stimulation.